A comparative study between the application of Bolam principle in Malaysia and Singapore / Nurul Atiqah Mohd Nor and Puteri Iskandariah Md Tahir - Mohd Nor, Nurul Atiqah; Md Tahir, Puteri Iskandariah (2007)
This project paper is regarding the application of Bolam principle in determining breach of duty of care as well as bringing to light the current test decided recently in Malaysia. Besides discussing on the application and rejection, this project paper will also touch on the breach of standard of care of medical practitioners. This project paper is divided into seven chapters; introduction on the Bolam principle, the law on medical negligence, breach of duty of care of professionals in Malaysia, application of Bolam principle in Singapore, application of Bolam principle in Australia, the pros and cons of Bolam principle and lastly the conclusion as well as recommendation on this topic. The aim of this project paper is to give an overview on the concept of Bolam test in determining the standard of care required of practitioners in performing their duties. In addition, this project paper attempt to analyse the pros and cons of the Bolam Principle as well as to study whether the rejection of Bolam Principle will reduce the number of medical negligence cases. Malaysia has rejected the application of Bolam principle recently for the case of Foo Fio Na. However Singapore is still applying the Bolam principle in determining the standard of care of the doctors. The scenario of medical negligence litigation in Malaysia is slowly picking up. As such, this project paper will also provide recommendations on how to reduce the medical negligence litigation. We hope that this project paper will be beneficial and enlightening to readers as well as able to raise more awareness among doctors and patients towards medical negligence